2022
DOI: 10.3390/antiox11030473
|View full text |Cite
|
Sign up to set email alerts
|

Important Functions and Molecular Mechanisms of Mitochondrial Redox Signaling in Pulmonary Hypertension

Abstract: Mitochondria are important organelles that act as a primary site to produce reactive oxygen species (ROS). Additionally, mitochondria play a pivotal role in the regulation of Ca2+ signaling, fatty acid oxidation, and ketone synthesis. Dysfunction of these signaling molecules leads to the development of pulmonary hypertension (PH), atherosclerosis, and other vascular diseases. Features of PH include vasoconstriction and pulmonary artery (PA) remodeling, which can result from abnormal proliferation, apoptosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 183 publications
(205 reference statements)
0
10
0
Order By: Relevance
“…The mitochondria is also regarded as the powerhouse of the cell because its function is to synthesize energy molecules in the form of ATP [ 33 ]. The mitochondria also plays a significant role in metabolic pathways such as beta-oxidation, pyruvate decarboxylation, ketogenesis, and apoptosis initiation accomplished via ROS generation and apoptotic proteins activation [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria is also regarded as the powerhouse of the cell because its function is to synthesize energy molecules in the form of ATP [ 33 ]. The mitochondria also plays a significant role in metabolic pathways such as beta-oxidation, pyruvate decarboxylation, ketogenesis, and apoptosis initiation accomplished via ROS generation and apoptotic proteins activation [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that phosphorylation and subsequent modulation of NOX activation may be regulated by protein kinase-C (PKC). Our laboratory has also shown that RISP-dependent mitochondrial ROS can activate PKCε and then NOX to induce further ROS generation, i.e., ROS-induced ROS generation (RIRG) [57,67,68]. Importantly, these studies support that mitochondrial ROS generation precedes non-mitochondrial ROS generators, such as NOX [69].…”
Section: Sources Of Rosmentioning
confidence: 62%
“…Redox signals or regulations of mt origin are also implicated in insulin resistance development in peripheral tissues [ 125 , 126 ]. Other listed examples include heart [ 127 , 128 , 129 ] and endothelial pathology [ 130 , 131 , 132 , 133 , 134 ], pulmonary hypertension [ 135 ], sepsis [ 136 ], skeletal muscle injuries (here, mt ROS signal for repair mechanisms, [ 137 , 138 ]), and NLR family pyrin domain-containing 3 (NLRP3)-related inflammatory states [ 139 , 140 , 141 ]. This list is illustrative and incomplete.…”
Section: Future Perspectivesmentioning
confidence: 99%